"Neoliberalism, Technocracy and Higher Education" Editors' Introduction. (4th July 2019) - Cruickshank, Justin; Abbinnett, Ross
ABSTRACT: This special issue of Social Epistemology has its origin in two symposia organised by the Contemporary Philosophy of Technology Research Group at the University of Birmingham (UK). These were 'The Digital University in a Neoliberal Age' in November 2017 and 'The Neoliberal Imagination' in February 2018. The articles published here explore the relationship between neoliberalism, technocracy and technology, with a special but not exclusive focus on universities, which are open to contestation concerning their role in the public sphere and the politics of knowledge production. Where universities are discussed, English higher education is focused on, because this is undergoing an intense audit-driven neoliberal re-engineering. English higher education is an outlier in Europe to the extent to which it has undergone marketisation, with top-down reforms imposed by the supposedly rolled back, less-interventionist neoliberal state (Shattock, Times Higher,  3 April 2019). Central to these are state-imposed technocratic audit regimes which are used to provide 'objective' data on 'performance', which has, always already, to be 'excellent' (see Readings' 1997 classic critique of the vacuity of the notion of 'excellence'). Before briefly introducing each article, we will situate the concerns mentioned above in the context of a social epistemological critique of knowledge production.